Kié̂p sau - Levy, Marc, 1961- (Nhà xuá̂t bản Hội nhà văn, 2006)
Jonathan is looking forward to marrying Christine, but a chance encounter upsets his life. He crosses paths with Clara, whom he already knew, probably in another life... A novel combining love, suspense, humor and the fantastic.